Cellulose nano-biocomposites from high oleic sunflower oil-derived thermosets. (June 2016) - Moreno, Maryluz; Armentano, Ilaria; Fortunati, Elena; Mattioli, Samantha; Torre, Luigi; Lligadas, Gerard; Ronda, Joan C.; Galià, Marina; Cádiz, Virginia
Graphical abstract: Highlights: Liquid easy to handle prepolymer/nanocellulose dispersions were formulated. Both monomers and nanofillers are of renewable origin. Films are cured under mild conditions. Good CNC dispersions in the polymer matrix were achieved. Properties improvement is notable in the nanocomposite with 5% CNC. Abstract: Thiol-Michael addition of pentaerythritol tetrakis(3-mercaptopropionate) (PE3MP) to a high oleic sunflower oil derivative containing enone groups (ETG), has been used to prepare vegetable oil derived renewable thermosets in an efficient way and under mild conditions. The same formulation has been used to prepare nano-biocomposites by incorporating into the polymerization mixture, 1 wt%, 5 wt% and 10 wt% of cellulose nanocrystals (CNC) modified with Beycostat A B09® as surfactant. The chosen methodology allows a good dispersion of the nano filler in a low polarity reactive media which still is a challenging approach. The morphological, thermal and mechanical properties of the different nano-biocomposites were evaluated and compared with the pristine thermoset. Morphological analysis shows that good dispersion of the nanofillers is achieved in all formulations. Mechanical properties show an improvement of the Young Modulus for all nanofiller contents, showing a maximum at 5 wt% loading (32 and 78 MPa for the pristine and 5% CNC nano-composite respectively) that has been related with the reinforcement effect of the modified CNC. CNC dispersion also affects positively the surface properties, thus reducing drastically the contact angle values (78.0–16.0° for the pristine and 10% CNC nano-composite respectively). Finally, protein adsorption was measured in order to evaluate potential application of these materials as biosensors and cell growing supports.